(untitled) (Journal of humanities and social sciences exploratio, 2026)
In recent years, the sharp rise in work stress among employees within the system has become a prominent issue affecting the governance efficiency of state-owned enterprises and the service quality of public sectors. Taking workplaces within the system under the background of shrinking incremental growth as its research object, this paper draws on organizational behavior, cognitive psychology, and public administration theories to systematically analyze the structural causes of work stress among employees within the system from three dimensions: economic structural transformation, internalization of cultural psychology, and rigid management mechanisms. The study finds that the downward transmission of macro-level resource constraints, the moralized construction of obedience under East Asian authoritarian culture, and the opacity of promotion rules interact to form a distinctive “stress complex” within the system, causing dual losses to employees’ mental health and organizational efficiency. On this basis, from the perspectives of fiscal and tax consulting and government procurement experts, this paper proposes a differentiated response path centered on “graded management of compliance stress” and “human-oriented performance evaluation,” with a view to providing references for human resource management practices in the context of deepening reform of state-owned enterprises.